Odpowiedzi

2009-11-30T21:10:38+01:00
A) ∫⅗x+½y=2
∫½(2x-y)=2
b) ∫x+y/2-x/3=4
∫x-y/2+y/3=-3

a)
⅗x+½y=2
0,6x+0,5y=2
0,5y=2-0,6x //:0,5
y= 4-1,2x
__________
½(2x-y)=2
x-0,5y=2
x-0,5(4-1,2x)=2
x-2+0,6x=2
1,6x=4
x=2,5
______________

y=4-(1,2*2,5)
y=4-3
y=1

b)∫x+y/2-x/3=4
∫x-y/2+y/3=-3

x+y/2-x/3=4
2/3x+1/2y=4
4/6x+3/6y=4
4x+3y=24
4x=24-3y
x=6-3/4y
_______________

x-y/2+y/3=-3
6-3/4y-1/2y+1/3y= -3
-9/12y-6/12y+4/12y= -9
11/12y=9
y=108/11=9i 9/11
__________________

x=6-(3/4*108/11)
x= 6-81/11
x= 66/11-81/11
x=-15/11= -1 i 4/11